Художня інтерпретація концепту слово у творчості Мирослава Дочинця - Лариса Кравець; Larysa Kravets; Kravec Larissza (Інститут української мови НАН України, 2024)
Резюме. У статті простежено специфіку художньої інтерпрета- ції ключового для прозових творів М. Дочинця концепту СЛО- ВО. Виявлено його текстові реалізації, що засвідчують бага- тогранність художньо-чуттєвого і філософського осягнення внутрішньої форми СЛОВА. Схарактеризовано асоціативні зв’язки лексеми СЛОВО в епітетно-метафоричних конструк- ціях, які виявляють оригінальність авторських інтерпретацій. З’ясовано, що СЛОВО для митця є каналом зв’язку з народом, його мовою і культурою, засобом збереження своєї національ- ної ідентичності, формою збереження культурно-історичної пам’яті, способом об’єднання мовної спільноти, інструмен- том спілкування і самовираження. Дослідження виконано на засадах лінгвософії.

Abstract. The concept of a word has a wide verbal representation and aestheticized expression in modern Ukrainian literature. In the process of active use, the semantic scope of the word is constantly changing, existing ones disappear and new associative connections arise, which serve as the basis for the formation of metaphors, metonymies, and comparisons. Artistic texts most fully reveal all the overtones of the word, its individual authorial interpretations. The features of the artistic understanding of the word in different time frames have repeatedly become the subject of scientific research. However, the concept of a word in the work of M. Dochynets has not yet been studied. In the work of M. Dochynets, the word is one of the key concepts. The author subtly feels its semantic scope and masterfully conveys semantic nuances. As in T. Shevchenko, in M. Dochynets, a word is not an abstract generalization, but a native word, the language of the native land, filled with the wisdom of the ages, rooted in the deep spiritual experience of a particular person and people, capable of expressing the most subtle movements of the soul and thought, causing excitement, and encouraging reflection. The author notes the beauty and originality of the language of the Transcarpathians. M. Dochynets emphasizes the spiritual essence of the word, its unifying role. With special respect, the artist writes about the specific vocabulary that preserves information collected by the language collective throughout its existence, records all the cultural heritage of the people – the native speakers. In the internal monologues and reflections of his characters, M. Dochynets uses a variety of linguistic means and techniques that characterize the peculiarities of the artist’s work on the word, reveal the difficulties that every writer faces. The word in the works of M. Dochynets exists not only in established linguistic, pragmatic, and cultural-sophical parameters. The artist defines a number of its other associative characteristics, namely smell, taste, color, sound. As a gourmet of the word, he especially appreciates the juicy folk word. The concept of the word in the prose of M. Dochynets is characterized as a linguistic, cultural-historical, psychological, spiritual phenomenon. The word for the artist is a marker of identity and a means of its preservation; a channel of communication with the people, their language, culture; a form of preserving cultural and historical memory; a way of uniting a language community; a tool of communication and self-expression.
Artistic interpretation of the concept of the word in the work of Myroslav Dochynеts
Редакційна колегія: https://ks.iul-nasu.org.ua/redaktsijna-kolegiya.html
Зміст: https://ks.iul-nasu.org.ua/vypusky-zhurnalu/2024-2/zbirnyk-kultura-slova-101-2024.html
Keywords: Мирослав Дочинець; концепт Слово; текст; твір; образ; образність